The Threshold Situation in Edvard Radzinsky’s Historical Parable „Lunin, or the Death of Jacques” - Zhurcheva, Olga (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article is devoted to the analysis of the historical parable Lunin, or the Death of Jacques, Recorded in the Presence of the Master by Edvard Radzinsky. Proceeding from the genre paradigm of the parable, Radzinsky builds the conflict of the play with the use of the threshold situation, with the main character awaiting execution. While expecting death, Lunin recalls his whole life, therefore the whole action of the play is concentrated in the real and in the mental time and space. Although in reality Lunin is alone in the prison cell, in his imagination he is surrounded by many people whom he has met in the course of his life. This plot paradox creates the illusion of the protagonist’s memories becoming visualised and of the public character of his death.